An Efficient and Green Synthesis of Flavones Using Natural Organic Acids as Promoter Under Solvent-free Condition - Thorat, Nitin M.; Kote, Santosh R.; Thopate, Shankar R. (Letters in Organic Chemistry, 2014)
An efficient and eco-friendly synthesis of flavones, promoted by naturally occurring acids, via cyclodehydration of 1-(2-hydroxyphenyl)-3-aryl-1,3-propanediones using conventional and microwave heating under solvent-free condition is described.
Keywords: naturally occurring acids